2019
DOI: 10.1080/00222895.2019.1649998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Task Constraints on Kinematic Synergies during Catching in Children with Developmental Delays

Abstract: Effects of a developmental task constraints intervention on kinematic synergies during two-hand catching in children with developmental delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Only a few of these tools are free-access (n=2/7, 28.6%). Most codes were implemented in Python (SCR_008394) and supported by libraries such as OpenGL (which produces 2D and 3D graphics) [29][30][31] and Numpy (SCR_008633) (which creates vectors and matrices, and mathematical functions) (45) that helps to process images that are captured in real-time and obtain an accurate representation of the movement.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few of these tools are free-access (n=2/7, 28.6%). Most codes were implemented in Python (SCR_008394) and supported by libraries such as OpenGL (which produces 2D and 3D graphics) [29][30][31] and Numpy (SCR_008633) (which creates vectors and matrices, and mathematical functions) (45) that helps to process images that are captured in real-time and obtain an accurate representation of the movement.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the results suggest that head movements can be used to evaluate catching skills that are not reflected in the catch rate. For example, in a previous study that examined catching motion using a motion capture system, reaching and catching motions during ball catching were measured to evaluate catching ability [ 24 ]. It is possible that head movements are also linked to the catching motion.…”
Section: Discussionmentioning
confidence: 99%
“…The strength and numbers of synergy might be changed because of developmental problems (Utley, Steenbergen, & Astill, 2007;Sekaran et al, 2012) and developmental delays (Parvinpour et al, 2019). For example, Parvinpour et al, (2019) identified two kinematic synergies in two-hand catching: one for reaching and one for catching. They also showed that one more synergy, retaining, emerged after the intervention in the transfer test.…”
Section: Introductionmentioning
confidence: 99%